VALIDASI METODE FLAME ATOMIC ABSORPTION SPECTROPHOTOMETRY (FAAS) UNTUK PENETAPAN KADAR BESI (Fe) DALAM SEDIAAN KAPSUL MULTIVITAMIN MINERAL - DEWI SULTHONIYAH, 051211131166 (2016)
METHOD VALIDATION OF FLAME ATOMIC ABSORPTION SPECTROPHOTOMETRY (FAAS) FOR DETERMINATION OF IRON (Fe) IN MULTIVITAMIN MINERAL CAPSULE DOSAGE FORM DEWI SULTHONIYAH Flame Atomic Absorption Spectrophotometry (FAAS) has been developed for determination of iron (Fe) in multivitamin mineral capsule dosage form. The method of sample preparation used combination of dry ashing (450 ± 20˚C for 2 hours or until it becomes ashes) and wet ashing with a mixture H2O2 30%, HCl 6N, and HNO3 65%. The method validation comprises of the study of selectivity, linearity, accuracy, and precision. The proposed method was linear over the concentration ranges of 2-8 μg/mL. The regression was y=0,0435x+0,0237 with the correlation coefficient (r) obtained for those regression is 0,9996 and the relative process standard deviation value (Vxo) is 1,39%. The accuracy of Fe was 100,12%. The precision coefficients of variation in the range 0,99% for repeatability and 0,83% for intermediate precision. The method was successfully applied for determination of iron (Fe) in multivitamin mineral capsule dosage form. Keywords : method validation, FAAS, iron, multivitamin mineral capsule